Identifying characteristics and causes of women injuries in Sleman: 2016-2019 HDSS data - Pidada, Ida Bagus Gede Surya Putra; Priyambodo, Dewanto Yusuf; Noormaningrum, Budiatri Retno (Universitas Gadjah Mada, 2021)
Purpose: To describe the demographic characteristics, injury characteristics, and factors causing injury, as well as the relationship between demographic characteristics and injury characteristics, and between demographic characteristics and factors causing injury to women in Sleman Regency. Methods: This research is an observational analytic study using data from 1027 respondents of HDSS Sleman with a cross-sectional design. Results: Most of the subjects were over 46 years old (52.4%), married (54.9%), the last education was senior high school (SLTA) or equivalent (34.7%), homemakers (24.4% ), and live in urban areas (80.7%). The most common injuries were minor injuries (66.8%), with the location of the incident on the highway (47.5%). All injuries were unintentional, with the most being motorcycle accidents (28.8%). Analysis of age and location of residence with injury characteristics showed a statistically significant relationship (p=0.000). The test results of all demographic characteristics with factors causing injury did not establish a statistically significant relationship. Conclusion: Demographic characteristics of injured women in Sleman are mostly over 46 years old (52.4%), married (54.9%), have high school education or equivalent (34.7%), working as housewives ( 24.4%), and live in urban areas (80.7%). Most of the locations where the injury occurred were on the highway (47.5%). Characteristics of the most frequent injuries were minor injuries (66.8%), and the most common factor causing unintentional injuries was motorcycle land transportation accidents (28.8%). There is a relationship between the characteristics of the age and location of women in Sleman with the injury category. There is no relationship between all demographic characteristics of women in Sleman with factors causing injury.